Aprovechamiento de los residuos sólidos orgánicos para la generación energía en Bogotá. (2022)
This paper proposes the use of organic solid waste for power generation, mainly in Bogotá. Where large amounts of organic waste are produced daily and do not have a correct disposal. Generating pollution in the ecosystem, affecting health, etc. Due to the decomposition of waste, these pose pathogenic microorganisms that generate diseases and some that are decomposers. On the other hand, the decomposition of these residues generates gases that are released into the atmosphere, causing greenhouse gases. This waste has great potential for energy generation, since it would be of great help to the environment because it generates a source of energy production with great potential, which contributes to more sustainable waste management. Thus preventing waste from releasing greenhouse gases and reaching the atmosphere. First, a contextualization and consolidation of information is carried out on the use of organic solid waste for the generation of energy, description and generalities of the waste, the environmental impacts that these may have, the current legal framework for the management of waste and finally techniques for the use of waste and which are used for power generation.